Police Provocation in the Practice of the Bulgarian Courts and the European Court of Human Rights - Hadzhiyska, Adelina (Law Journal of New Bulgarian University, 2024)
This article examines "police provocation" in the practice of Bulgarian courts and the European Court of Human Rights (ECHR). Knowledge of this procedural institution is important for successfully distinguishing it from various legitimate means of proof in order to avoid abuses by the state authorities. The criteria for the identification of police provocation applicable in criminal cases are discussed. Attention has been paid to the mechanism developed by the ECHR for compensation of admitted violations of the right to a fair trial under Art. 6 § 1 ECHR by excluding evidentiary materials acquired through "provocation" by the public authorities.